Analisis Kesulitan Belajar Berbasis Komunikasi Dalam Jaringan (daring) Siswa Kelas IV Selama Masa Pandemi Covid-19 - Tamara Putri Rafendi; Rahman Eri Pridana; Luthfi Hamdani Maula (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2020)
The aim of this study was to obtain information objectively about the difficulties of online-based learning fourth grade students of MI Cibolang Kidul based on the policy to study at home during the Covid-19 pandemic. The approach of this study was decrictive qualitative method. Indirect Communication techniques were used as the instruments of collecting the data with data collecting tools by distributing interviews used Google Form media. The informants in this study were 42 students and only 36 students were filled in. The results showed that the difficulties of online-based learning during the Covid-19 pandemic are very diverse. Various obstacles that make online-based learning difficulties include learning support facilities such as personal cellphones are still lacking, limited access to internet, limited celluler data quota, teacher's explanation is not optimal and the role of parents is very important to assist in online-based learning.